Emergent crisis of antibiotic resistance: A silent pandemic threat to 21st century. (January 2023) - Akram, Fatima; Imtiaz, Memoona; Haq, Ikram ul
Abstract: Antibiotic resistance has become an indispensably alarming menace to the global community. The primary factors are overuse and abuse of antibiotics, lack of novel medicines under development, the health care industry's focus on profit, and the absence of diagnostic testing prior to the prescription of antibiotics. Additionally, over the past few decades, the main factors contributing to the global spread of antibiotic resistance have been the overuse of antibiotics in livestock and other animals, drug efficacy, development of fewer new vaccines, environmental toxicity, transmission through travel, and lack of funding for healthcare research and development. These factors have accelerated resistance in microorganisms through structural and functional modifications in bacteria such as reduced drug permeability, increased efflux pumps, enzymatic antibiotic modification, and change in drug target, intracellular infection, and biofilm creation. There has been an increase in resistance during the pandemic and among cancer patients due to improper prescriptions. A number of modern therapeutic alternatives have been developed to curb widespread antibiotic resistance such as nanoparticle, bacteriophage, and antimicrobial biochemical approaches. It is high time to explore new alternatives to curtail enormous increase in resistant pathogens which could be an incurable global confrontation. This review highlights the complete insight on the global drivers of resistance along with the modes of action and impacts, finally discussing the latest therapeutic alternatives. Graphical abstract: Image 1 Highlights: Globally, public faces the unavoidably grave threat of antibiotic resistance. The main factors of resistance are misuses, less effectiveness and lack of new drugs. To reduce this, a variety of contemporary medicinal alternatives have been created. The world needs to search for new options to stop massive rise in diseases.